Encapsulation of Vecuronium and Rocuronium by Sugammadex Investigated by Surface-Enhanced Raman Spectroscopy - Adriana Kenđel; Ivo Piantanida; Snežana Miljanić (Molecules)
Aiming toward a novel, noninvasive technique, with a real-time potential application in the monitoring of the complexation of steroidal neuromuscular blocker drugs Vecuronium (Vec) and Rocuronium (Roc) with sugammadex (SDX, medication for the reversal of neuromuscular blockade induced by Vec or Roc in general anesthesia), we developed proof-of-principle methodology based on surface-enhanced Raman spectroscopy (SERS). Silver nanoparticles prepared by the reduction of silver ions with hydroxylamine hydrochloride were used as SERS-active substrates, additionally aggregated with calcium nitrate as needed. The Vec and Roc SERS spectra were obtained within the biorelevant 5 × 10−7–1 × 10−4 M range, as well as the SERS of SDX, though the latter was observed only in the presence of the aggregating agent. SDX/drug complexes at a 1/1 molar ratio revealed significant spectral changes in the vibrational bands of the SDX glucose rings and the drug steroid rings, implying that the insertion of Vec and Roc molecules into the SDX cavity was not only driven by attractive electrostatic interactions between the positively charged cyclic unit of the drug and the negative carboxylate groups of cyclodextrin but also supported by hydrophobic interactions between the host cyclodextrin and the guest drug molecule. The observed changes in SERS signals are applicable in biorelevant conditions and support further studies of SDX/drug complexes in vivo.